Kegiatan Ekstrakurikuler Karate Untuk Membentuk Kedisiplinan Siswa Di SD - Bondhan Pamungkas (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2013)
Abstract: This research aims to observe the contribution of karate as an extracurricular activity to building the discipline of the upper class students in Negarahada 01 Public Elementary School, Bumiayu Subdistrict. This research employed a descriptive qualitative method. The data were gained by using interview, observation, and documentation. Afterwards, the data were collected by using technique and data source triangulation and were analyzed by using an inductive data analysis technique. The result of the research reveals that the karate training has positive contribution to building the discipline of the upper class students of Negarahada 01 Public Elementary School, Bumiayu Subdistrict. The students who join the karate training are more disciplined than the others who do not. The discipline is shown through some attitudes such as joining flag ceremony orderly, arriving at school punctually, dressing neatly according to the school’s regulation, obeying the teachers, keeping cleanliness, not playing truant, not involving in any affrays, not smoking, not being noisy during classes or recess, and obeying the school’s activity schedule. Keywords : karate extracurricular activity, character, discipline.